Experticia, vaguedad y máximas de la experiencia en los casos de elusión fiscal - Osorio Morales, Hugo; Toledo Zúñiga, Patricia (Pontificia Universidad Católica del Perú, 2024)
The main objective of this research is to analyze vagueness as an evidentiary problem in tax avoidance cases, evaluating its impact on the ability of the adjudicating body to determine whether the specific facts of a case can be classified as tax avoidance. The work also aims to explain that the expertise of tax law applicators is relevant, both to identify and resolve problems of vagueness and to make and evaluate maxims of experience in establishing the facts in this type of cases. To this effect, in the first section, an attempt is made to delimit the concept of “tax avoidance” and a definition of tax avoidance consistent with the dominant linguistic uses in current Spanish and Chilean dogmatics. The second section analyzes the role of vagueness, frequently used in the application of general anti-avoidance rules, to combat tax avoidance. It is concluded that it is a kind of vagueness called “extravagant”, used intentionally by the legislator to try to regulate the innumerable forms in which the avoidance phenomenon can be manifested. The third section studies the importance of expertise and the maxims of experience to distinguish an elusive case from a non-elusive case.

El objetivo principal de esta investigación es analizar la vaguedad como un problema probatorio en casos de elusión fiscal, evaluando su impacto en la capacidad del órgano juzgador para determinar si los hechos específicos de un caso pueden ser clasificados como elusivos. El trabajo, además, pretende explicitar que la experticia de los aplicadores del derecho tributario es relevante, tanto para identificar y resolver los problemas de vaguedad como para realizar y evaluar máximas de la experiencia en el establecimiento de los hechos en este tipo de casos. Para este efecto, en la sección primera se intenta delimitar el concepto de «elusión fiscal» y se propone una definición de elusión fiscal consistente con los usos lingüísticos dominantes en la dogmática española y chilena actual. En la sección segunda se analiza la función de la vaguedad, frecuentemente usada en los supuestos de aplicación de las normas generales antielusivas, para intentar combatir la elusión fiscal. Se concluye que se trata de una clase de vaguedad denominada «extravagante», utilizada intencionadamente por el legislador para intentar regular las innumerables formas en que puede presentarse el fenómeno elusivo. En la sección tercera se estudia la importancia de la experticia y las máximas de la experiencia para distinguir un caso elusivo de un caso no elusivo.
Expertise, Vagueness and Maxims of Experience in Tax Avoidance Cases
Keywords: Tax avoidance; Vagueness; Expertise; General Anti-Avoidance Rule; Elusión fiscal; Vaguedad; Experticia; Norma general antielusiva; https://purl.org/pe-repo/ocde/ford#5.05.01